Legal Review of the Legal Status of Co-Assistant in the Teaching Hospital According to Law No. 17 of 2023 Concerning Health - Alza Hamonangan Pasaribu; T Riza Zarzani; M Arif Sahlepi (Indonesian Journal of Multidisciplinary Sciences (IJoMS), 2026)
Professional medical education in Indonesia requires medical graduates to undergo a professional phase (co-ass) at a teaching hospital. At this stage, professional students perform clinical procedures under the supervision of a clinical supervisor. Education in hospitals raises new issues between education for professional students and patient safety. Law No. 17 of 2023 concerning Health has become a new reference for all issues in the world of health. As knowledge develops, patient awareness of their rights increases. Patients demand better services accompanied by clear legal protection. This study aims to analyze the legal status of professional students in teaching hospitals based on Law No. 17 of 2023 concerning Health, focusing on aspects of legal protection and the implementation of applicable norms. The results show that existing regulations are inadequate in detailing the status of professional students.co-ass in teaching hospitals. Therefore, coordination between relevant parties is needed to establish clear regulations for professional students in Law No. 17 of 2023 to create a safe environment for both co-ass and patients.